Brain Trauma, PET Scans and Forensic Complexity. (16th October 2013) - Moriarty, Jane Campbell; Langleben, Daniel D.; Provenzale, James M.; Granacher, Robert P.; Sweet, Jerry J.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> Positron Emission Tomography (PET) is a medical imaging technique that can be used to show brain function. Courts have admitted PET scan evidence in cases involving brain damage, injury, toxic exposure, or illness ("brain trauma") and to support claims of diminished cognitive abilities and impulse control. Despite the limited data on the relationships between PET, brain trauma and behavior, many courts admit PET scan evidence without much critical analysis. This article examines the use of PET as proof of functional impairment and justification of abnormal behavior by explaining its diagnostic use and limitations, the limited support for claims of its relationship to behavior, and evidentiary considerations that should govern its admission into court as evidence. The authors urge courts to consider PET evidence, claims of experts, and the scope of the proposed testimony with greater deference to the clinical scope of PET, as outlined by the American College of Radiology's appropriateness criteria and the Working Group Report of the American Psychiatric Association. Copyright © 2013 John Wiley & Sons, Ltd.